2017
DOI: 10.1016/j.neurobiolaging.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Age-related deficits in auditory temporal processing: unique contributions of neural dyssynchrony and slowed neuronal processing

Abstract: This study was guided by the hypothesis that the aging central nervous system progressively loses its ability to process rapid acoustic changes that are important for speech recognition. Specifically, we hypothesized that age-related deficits in neural synchrony and neuronal oscillatory activity occur independently in older adults and disrupt auditory temporal processing. Neural synchrony is largely dependent on phase locking within the central auditory pathway, beginning at the auditory nerve. In contrast, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 69 publications
(94 reference statements)
4
21
0
Order By: Relevance
“…Older adults' P1 and N1 component amplitudes were significantly larger compared to younger adults, yet their P2 peaks were reduced. These findings are consistent with previous reports of age-related changes in AEP amplitude (Anderer et al, 1996;Czigler et al, 1992;Harkrider et al, 2005;Henry et al, 2017;Rufener et al, 2014;Tremblay et al, 2003), which may be attributed to age-related changes at the cellular level (Caspary et al, 2008;de Villers-Sidani et al, 2010;Hughes et al, 2010) or neuronal synchrony (Anderson et al, 2012;Harris and Dubno, 2017).…”
Section: Age-related Changes In the Timing Of Brain Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…Older adults' P1 and N1 component amplitudes were significantly larger compared to younger adults, yet their P2 peaks were reduced. These findings are consistent with previous reports of age-related changes in AEP amplitude (Anderer et al, 1996;Czigler et al, 1992;Harkrider et al, 2005;Henry et al, 2017;Rufener et al, 2014;Tremblay et al, 2003), which may be attributed to age-related changes at the cellular level (Caspary et al, 2008;de Villers-Sidani et al, 2010;Hughes et al, 2010) or neuronal synchrony (Anderson et al, 2012;Harris and Dubno, 2017).…”
Section: Age-related Changes In the Timing Of Brain Activitysupporting
confidence: 93%
“…With advancing age listening becomes more challenging, particularly in "cocktail party" scenarios (de Villers-Sidani et al, 2010;Pichora-Fuller et al, 2017;Rossi-Katz and Arehart, 2009). This difficulty could arise from age-related changes in peripheral and central auditory processes (Anderson et al, 2013;Clinard et al, 2010;Clinard and Cotter, 2015;Harris and Dubno, 2017), such as the poorer encoding in early sensory regions (Grose and Mamo, 2012;He et al, 2007;Mahajan et al, 2017;Paraouty et al, 2016;Wallaert et al, 2016). Changes in higher cognitive processes may also influence older adults' performance via top-down feedback (Henry et al, 2017), through reduced attentional flexibility (Nunez et al, 2015;Zanto and Gazzaley, 2014), or changes in decision criteria when reporting perceptual performance (Dully et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We interpret this as a mechanism for strengthening the internal representations of temporally degraded signals by engaging top-down cognitive resources. Congruent with these interpretations, previous human and animal studies also describe age-related losses in auditory temporal processing and an inability to accurately localize sound in cluttered environments (Pichora-Fuller et al 2007;Dubno et al 2008;Eddins & Hall, 2010;King et al 2014;Harris & Dubno, 2017). Speech in noise conditions degrades speech understanding even in older individuals with healthy hearing (Pichora-Fuller et al 1995).…”
Section: Effects Of Ageing On Central Auditory System and Top-down Prmentioning
confidence: 96%
“…The use of the diagnostic term presbycusis ("elderly hearing") to refer to ARHI reflects the common assumption that the speech processing difficulties of older persons should be predictable from their cochlear audiometric configuration (Pacala & Yueh, 2012;Schuknecht & Gacek, 1993). However, clinical interventions aimed at compensating for peripheral hearing loss (e.g., hearing aids) often do not provide adequate benefit for many older patients, suggesting that peripheral and central ARHI are distinct conditions (Gates, 2012;Harris & Dubno, 2017). In humans, however, it is difficult in practice to disentangle the possible interactions between auditory sensory processing and cognitive influences (American Academy Of Audiology, 2010;Humes et al, 2009Humes et al, , 2012Humes et al, , 2013Recanzone, 2018).…”
mentioning
confidence: 99%
“…The gap detection threshold (GDT) has been established as the single most common measure of central auditory temporal processing because cognitive influence is minimal, making gap detection potentially ideal for disentangling peripheral and central ARHI (Creelman, 1962;Divenyi & Hirsch, 1974;Preece & Tyler, 1989;Gordon-Salant & Fitzgibbons, 1999;Frisina, 2001;Schoof & Rosen, 2014). Subsequent studies have clearly demonstrated longer GDTs in older populations (Harris & Dubno, 2017;Ozmeral, Eddins, Frisina, & Eddins, 2016;Palmer & Musiek, 2014). However, the question of whether central ARHI could exist independently of peripheral hearing loss remains to be addressed.…”
mentioning
confidence: 99%